2009
DOI: 10.1002/art.24849
|View full text |Cite
|
Sign up to set email alerts
|

Elevated insular glutamate in fibromyalgia is associated with experimental pain

Abstract: Objective. Central pain augmentation resulting from enhanced excitatory and/or decreased inhibitory neurotransmission is a proposed mechanism underlying the pathophysiology of functional pain syndromes such as fibromyalgia (FM). Multiple functional magnetic resonance imaging studies implicate the insula as a region of heightened neuronal activity in this condition. Since glutamate (Glu) is a major cortical excitatory neurotransmitter that functions in pain neurotransmission, we undertook this study to test our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
231
7
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 289 publications
(250 citation statements)
references
References 29 publications
7
231
7
5
Order By: Relevance
“…12,13 Interestingly, the current authors' group demonstrated that the degree of enhanced pain sensitivity in FM is associated with elevated levels of combined glutamate (Glu), an excitatory neurotransmitter, and glutamine (Gln; combination, Glx) within the insula, a brain region involved in higher-order sensory processing. 14,15 These data have led the current authors and other researchers to speculate that elevated excitatory neurotransmission may play a role in enhanced pain sensitivity in FM. However, the role of this enhanced sensitivity in treatment response has largely been unexplored.…”
Section: Introduction Rmentioning
confidence: 74%
“…12,13 Interestingly, the current authors' group demonstrated that the degree of enhanced pain sensitivity in FM is associated with elevated levels of combined glutamate (Glu), an excitatory neurotransmitter, and glutamine (Gln; combination, Glx) within the insula, a brain region involved in higher-order sensory processing. 14,15 These data have led the current authors and other researchers to speculate that elevated excitatory neurotransmission may play a role in enhanced pain sensitivity in FM. However, the role of this enhanced sensitivity in treatment response has largely been unexplored.…”
Section: Introduction Rmentioning
confidence: 74%
“…Although the results of these studies are not homogeneous, [21][22][23][24][25][26][27] because of the different MRS protocols, magnetic fields used, and areas of study, in 4 of these, alterations of the glutamatergic system were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some MRS studies [21][22][23][24][25][26][27] have demonstrated alteration of cerebral metabolites in patients with FM, and though the results are not homogeneous, they strengthen the hypothesis of a neural dysfunction secondary to the pain processing.…”
mentioning
confidence: 99%
“…23,21 Findings of generalized hyperalgesia (an increased response to painful stimuli) and allodynia (painful response to a non-painful stimuli) are also present in fibromyalgia. 14,17 We hypothesized that the enhanced brain response seen in women with FM compared to HCs in pain related regions such as the insula cortex, somatosensory, dorsolateral prefrontal cortex, thalamus and cingulate cortex, 17,9 may also be present in individuals with VVD, if these two pain conditions have similar pathobiology, as suggested by the observed generalized hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%